Effect of Different Amounts of TiF3 on the Reversible Hydrogen Storage Properties of 2LiBH4–Li3AlH6 Composite - Li, Yun; Zhang, Yuxian; Chen, Lixin (Frontiers in Chemistry, 2021)
Hydrogen is a potential green alternative to conventional energy carriers such as oil and coal. Compared with the storage of hydrogen in gaseous or liquid phases, the chemical storage of hydrogen in solid complex hydrides is safer and more effective. In this study, the complex hydride composite 2LiBH4–Li3AlH6 with different amounts of TiF3 was prepared by simple ball-milling and its hydrogen storage properties were investigated. Temperature programmed desorption and differential scanning calorimetry were used to characterize the de/rehydrogenation performance, and X-ray diffraction and scanning electron microscopy (SEM) were used to explore the phase structure and surface topography of the materials. The dehydrogenation temperature decreased by 48 °C in 2LiBH4–Li3AlH6 with 15 wt % TiF3 composites compared to the composite without additives while the reaction kinetics was accelerated by 20%. In addition, the influence of hydrogen back pressure on the 2LiBH4–Li3AlH6 with 5 wt% TiF3 composite was also investigated. The results show that hydrogen back pressure between 2.5 bar to 3.5 bar can improve the reversible performance of the composite to some extent. With a back pressure of 3.5 bar, the second dehydrogenation capacity increased to 4.6 wt % from the 3.3 wt % in the 2LiBH4–Li3AlH6 composite without hydrogen back pressure. However, the dehydrogenation kinetics was hindered. About 150 h, which is 100 times the time required without back pressure, was needed to release 8.7 wt % of hydrogen at 3.5 bar hydrogen back pressure. The SEM results show that aluminum was aggregated after the second cycle of dehydrogenation at the hydrogen back pressure of 3 bar, resulting in the partial reversibility of the 5 wt % TiF3-added 2LiBH4–Li3AlH6 composite.